2006
DOI: 10.1016/j.jana.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ice Massage on Neuropathic Pain in Persons With AIDS

Abstract: Peripheral neuropathic pain is a unique form of chronic pain that afflicts up to 50% of persons with AIDS. The purpose of this pilot study was to examine the effects of ice massage to reduce neuropathic pain and improve sleep quality and to determine the feasibility of a larger study. A repeated measures design was used. The three treatments consisted of ice massage, dry-towel massage, and presence. Consecutive sampling was used to select 33 persons with AIDS who had neuropathic pain. Although the results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Perhaps owing to the ease of use of the RCSQ, it has also been used in other patient groups, such as lactating mothers, 34 hospitalised elders, 35 patients with AIDS, 36 hospitalised patients with mental health disorders, 37 and also relatives of palliative care patients at home. 38 However, the validity of the RCSQ was not discussed in the aforementioned studies performed outside the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps owing to the ease of use of the RCSQ, it has also been used in other patient groups, such as lactating mothers, 34 hospitalised elders, 35 patients with AIDS, 36 hospitalised patients with mental health disorders, 37 and also relatives of palliative care patients at home. 38 However, the validity of the RCSQ was not discussed in the aforementioned studies performed outside the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…Hot and cold applications could also be used together as in contrast baths. 8 There is another study that has investigated the role of massage in spinal cord injury (SCI) patients. All these superficial heat agents should not be applied in high degrees because of possible risk for increase in pain.…”
Section: Physical Therapy Modalitiesmentioning
confidence: 99%
“…Desensitization techniques (e.g., ice massage, dry-towel massage) have shown little effect. 22 A systematic review, not specific to HIV and comprising three studies, indicated that resistive exercises may moderately improve muscle strength among people with peripheral neuropathy. 23 Compensatory strategies such as adaptive footwear have been used to increase support and cushioning to relieve pain.…”
Section: Management Of Neuropathymentioning
confidence: 99%